2012
DOI: 10.3174/ajnr.a3285
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Plaque Characterization Using CT Multienergy Imaging

Abstract: BACKGROUND AND PURPOSE:Carotid artery plaque types can be categorized with CT according to their HU values. The purpose of this work was to analyze carotid artery plaque characteristics by using multienergy imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
(21 reference statements)
3
14
0
Order By: Relevance
“…These results were consistent with the previous study performed by Saba et al. 28 However, we did not see this characteristic for the FN feature, as the C F-FN for all energy spectra for the CT systems were not very different. Energy bins j ¼ 2 of DT-2 were the highest as compared to other energy bins for MECT-PC in both reconstructed images.…”
Section: Simulation Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…These results were consistent with the previous study performed by Saba et al. 28 However, we did not see this characteristic for the FN feature, as the C F-FN for all energy spectra for the CT systems were not very different. Energy bins j ¼ 2 of DT-2 were the highest as compared to other energy bins for MECT-PC in both reconstructed images.…”
Section: Simulation Resultssupporting
confidence: 83%
“…Specifically, this observer design was similar to the way that a radiologist views multiple energy windows of spectral CT images to investigate attenuation values of a tissue at multiple energy levels. In the study reported by Saba et al, 28 they showed that the HU values of each plaque type (e.g., fatty, mixed, and calcified) should be classified according to the energy level because the HU values of plaque significantly change with the selected kiloelectron volt. Our observer design was motivated by Platisa et al and Chen et al, who built and validated a sophisticated two-layered numerical observer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saba et al [106] assessed ''in vivo'' the effect of the multispectral imaging in terms of carotid artery plaque classification and found that the HU values of carotid artery plaque significantly change according to the selected keV. Results from this study demonstrated that the HU-based plaque type (fatty and mixed) classification can be improved with the use of multienergy imaging.…”
Section: Dual-energy Imagingmentioning
confidence: 71%
“…However, the attenuation values of various types of plaques (calcified, noncalcified, or mixed) overlap as a result of contrast enhancement, motion artifact, and partial volume effect. These limitations are amplified when the tube voltage is modified (54).…”
Section: Characterization Of Plaquementioning
confidence: 99%